Initial teacher education in Russia: connecting theory, practice and research - Valeeva, Roza A.; Gafurov, Ilshat R. (European Journal of Teacher Education, 2017)
This paper explores initial teacher education (ITE) in Russia, its organisation and content in the light of international literature. Changes in the political, socio-economic and cultural life of Russia in recent decades have defined a completely different model of teacher education. This model has evolved through key policy documents including the ‘Conception of pedagogical education development support (2013; http://minobrnauki.rf/documents/3871); ‘The teacher professional standard’ (2013; http://www.rosmintrud.ru/docs/mintrud/orders/129/), and, in 2014, the ‘Comprehensive programme to improve the professional skills of educational institutions teaching staff (http://www.consultant.ru/document/cons_doc_LAW_166654/). These documents have led to important changes in teacher education policy with serious consequences in terms of structure and curriculum. A key objective of this paper, therefore, is to examine the structure and curriculum of ITE in Russia within competency-based approach. The article also explores how the research dimension is integrated in ITE programmes, as well as new concepts and approaches linking theory and practice. In outlining the new model, the approach to teacher education followed by Kazan Federal University is used an illustrative example.